Development of a Da’wah Model through the Use of Regression Modelling: Case Studies in Kelantan - Wan Ab Majid, Wan Mahmood (MENARA : Journal of Islamic and Contemporary Issues, 2025)
This study aims to develop an effective da'wah model through the use of regression modelling, focusing on various factors that influence the effectiveness of da'wah among non-Muslim communities in Kelantan, Malaysia. Five main regression models were developed and analyzed, each of which relates critical aspects in the acceptance and appreciation of Islamic teachings such as faith knowledge, worship, cultural appreciation, criminal fiqh, and Islamic economic principles. The method used in this study is a quantitative method with a descriptive statistical approach. Data collection techniques through observation, questionnaires, documentation. The results of the study found that the importance of faith is the most influential factor in shaping cultural appreciation and understanding of Islamic practices. This study can provide valuable insights into how these factors interact and offer practical suggestions for improving da'wah strategies based on empirical data. In addition to serving as a guide for a more targeted and context-sensitive approach to da'wah, increasing the acceptance and understanding of Islam among non-Muslims in Kelantan.